Development of low-speed wind energy harvesting device. (December 2022) - Younis, Adel; Dong, Zuomin; Badawy, Mohamed El; Khatib, Fadi Al; Anazi, Abeer Al
Abstract: Since the energy demand increases, the sources of fluid energy such as wind energy and marine energy have attracted widespread attention, especially vortex-induced vibrations (VIV) excited by wind energy. This paper proposes a wind energy harvesting device-based VIV concept. The proposed device converts the mechanical energy of the oscillator into electrical energy. Different design shapes, that motivates disturbance in airflow, were proposed and tested. The proposed designs were numerically and experimentally tested to gauge their performance and efficiency in generating power. The detailed design and analysis for VIV including computational fluid dynamics (CFD) simulation were carried out. The CFD simulations were concentrated on the elastic rod (mast), which represents the critical component of the proposed model. Wind tunnel was used to conduct the experimental work. Piezoelectric sensors were utilized to measure and monitor extracted power. The best location of the piezoelectric sensors on the mast was investigated and located. The results of the simulations are reported in this paper. For each simulated case, lift coefficient, velocity, pressure, and vorticity contours are presented. It was also concluded that adding complexity to the geometry of the cylindrical proposed design would increase the lift force, and therefore, increasing the power. Promising numerical and experimental results were obtained, and power generation was maximized.